Higher Education in Iraq and the Requirements of Development and the Labour Market - Kadhim, Asst.L. Rand Ayad Kadhim; Mahdi, Asst.L. Ikhlas Reda Mahdi (Sulaimani Journal for Humanities, 2026)
Higher education is considered one of the most crucial factors for the cultural, economic, and intellectual progress and development of societies. It provides individuals with experiences, skills, and general knowledge, including creating motivation for creativity, renewal, and innovation. Consequently, it leads to improving societal conditions, making educational institutions more effective in the process of social change. The expansion and development of these institutions themselves indicate improvements in living standards, a decline in illiteracy rates, and the eradication of poverty through work development, creativity, and the advancement of modern technology. Undoubtedly, the true development begins with education, as it supports the motivations formed by acquired knowledge through learning behavioral patterns that become part of social habits. From a sociological perspective, education refers to the gradual formation of cultural knowledge that either reinforces or weakens the motivations that integrate behavior models into habits. Education is also defined as the transmission of knowledge from one generation to another. Our world today witnesses many changes, where academic qualification is no longer the sole demand of education; instead, forming the public is also a crucial requirement. Thus, education in general, and higher education in particular, play an important role in development and social peace. It has become an undeniable fact that universities play a leading and positive role in achieving development in all societies, regardless of their social and economic systems. The mission of higher education is no longer limited to achieving traditional goals such as seeking, rooting, and disseminating knowledge but has extended to encompass all aspects of social, economic, political, scientific, and technological life.
Keywords: Education; Higher Education Institutions; Development; Labour Market